The influence of financial literacy, financial attitude and lifestyle on personal financial management of students at Batam International University - Apunlawan, Intan Larasati; Husda, Anggun Permata (Junal Ilmu Manajemen, 2025)
Financial management is closely related to managing finances in everyday life, both individuals and groups with certain goals. Personal financial management is very much needed because good financial management may be used as a guideline for someone to minimize consumptive behavior. This research aims to investigate more about the impact of financial literacy, financial attitudes and lifestyle on personal financial management. The study method used is quantitative using a non-probability sampling technique approach. The population or sample used in the study were accounting students at Batam International University with a total of 100 respondents. Data was obtained by distributing questionnaires directly via Google Form, which was then analyzed using the SPSS version 27 application. The results of the research explain that financial literacy, financial attitudes and lifestyle have a positive and significant effect on personal financial management. In addition, this study also found that financial literacy, financial attitudes and lifestyle together have a positive and significant effect on personal financial management.